Penyuluhan Kesehatan Memilah Jajanan Makanan Agar Terhindar Dari Penyakit Diare - Zafrida Siska (CV. Multi Kreasi Media, 2022)
School-age children need adequate food in quantity and quality in order to have a good nutritional status. They tend to buy food without concern for food hygiene. There are a lot of convenience food to be seriously considered by communities because it frequently contains harmful chemicals or biological contamination. Consequently, the children are at risk of unhealthy food consumption. This problem arises due to lack of knowledge about food safety. It results in health problems like diarrhea, cancer or even child growth disorder. Based on a survey of Indonesian food and drug authority in 2014, there were still problems associated with food standards and safety. This became a great concern because it deals with not only nutritional need but also nutritional values for optimal child growth. Method applied was health promotion at Hikmah orphanage Rumbai. The result of this promotion obtained increased average score of knowledge about healthy convenience food before and after the event. It was expected to be the foundation for clean and healthy living behavior at schools resulting in healthier generation.